Kajian Perencanaan Pembangkit Listrik Tenaga Surya Untuk Budidaya Ikan - Mhd. Ilyasa Lubis; Dino Erivianto; Rahmaniar (CV. Hawari, 2025)
Sukaraya Village, Pancur Batu District, has great potential in the fisheries cultivation sector. Activities such as aeration and water pumping require reliable and efficient energy sources. Solar Power Plants (PLTS) are a sustainable solution that can overcome these obstacles, considering the abundant availability of sunlight in this area. This study aims to design an optimal PLTS system to support fish farming operations in Sukaraya Village. The design is carried out by considering the power needs of the fisheries system, the potential of solar energy, and the efficiency and reliability of the PLTS components. Based on the research results, the PLTS components consist of 15 pcs of 100 Wp polycrystalline solar panels, a 100 A solar charge controller, 4 12V 150Ah batteries, and an inverter capacity of 7000A. The results of calculations in the PLTS planning can distribute electricity with a load capacity of 5,760Wh. The results of the calculation of the overall cost required in the planning of a solar power plant for fish farming are Rp. 51,912,967